Предмет: Математика, автор: karina2006444

2 целых 18\43 + х = 3 целых 4\43​

Ответы

Автор ответа: NNNLLL54
1

Пошаговое объяснение

2\frac{18}{43}+x=3\frac{4}{43}\\\\x=3\frac{4}{43}-2\frac{18}{43}\\\\x=(3+\frac{4}{43})-(2+\frac{18}{43})\\\\x=(3-2)+(\frac{4}{43}-\frac{18}{43})\\\\x=1-\frac{14}{43}\\\\x=\frac{43}{43}-\frac{14}{43}\\\\x=\frac{29}{43}


Аноним: в уравнении + х
Автор ответа: Аноним
2

Ответ:

Пошаговое объяснение:

2 18/43 + х = 3 4/43

х = 3 4/43 - 2 18/43

х = 2 47/43 - 2 18/43   (3 4/43 = 1 + 2 4/43 = 2 + 43/43 + 4/43 = 2 47/43)

х = 29/43

Ответ: 29/43

Похожие вопросы
Предмет: Химия, автор: qp48x8gq4s